What if? The Economic Effects for Germany of a Stop of Energy Imports from Russia - Rüdiger Bachmann; David Baqaee; Christian Bayer; Moritz Kuhn; Andreas Löschel; Benjamin Moll; Andreas Peichl; Karen Pittel; Moritz Schularick (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
This article discusses the economic effects of a potential cut-off of the German economy from Russian energy imports. We show that the effects are likely to be substantial but manageable. In the short run, a stop of Russian energy imports would lead to a GDP decline in range between 0.5% and 3% (cf. the GDP decline in 2020 during the pandemic was 4.5%). – – In diesem Artikel werden die wirtschaftlichen Auswirkungen eines möglichen Stopps russischer Energieimporte auf die deutsche Wirtschaft diskutiert. Wir zeigen, dass die Auswirkungen wahrscheinlich substanziell, aber handhabbar sein werden. Kurzfristig würde ein Stopp der russischen Energieimporte zu einem BIP-Rückgang zwischen 0,5 % und 3 % führen (Zum Vergleich: Der BIP-Rückgang im Jahr 2020 auf Grund der Pandemie betrug 4,5 %).
Keywords: 330